2020
DOI: 10.1371/journal.pone.0231445
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of C-reactive protein in dogs undergoing medial patellar luxation surgery

Abstract: C-reactive protein (CRP) is a major acute phase protein used to monitor response to treatment during surgical recovery. Depending on the anatomical problem, surgery type and technique, the level of CRP can change drastically. The aim of this study was to describe the changes in CRP and white blood cell (WBC) levels following surgery for medial patellar luxation in otherwise healthy dogs. Twenty-two dogs completed the study. CRP was measured using a commercially available dry chemistry slide on a commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The present study was conducted on dogs considered healthy by clinical and laboratory tests, including complete blood counts and serum biochemistry profiles. Among the orthopedic diseases, MPL and CCLR were included in the orthopedic group because most of these diseases were chronic and generally not accompanied by elevated pre-operative CRP levels [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was conducted on dogs considered healthy by clinical and laboratory tests, including complete blood counts and serum biochemistry profiles. Among the orthopedic diseases, MPL and CCLR were included in the orthopedic group because most of these diseases were chronic and generally not accompanied by elevated pre-operative CRP levels [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of CRP in dogs showed similar results compared to human medicine [11,12]. A previous study that compared the factors participating in the acute-phase response in dogs undergoing elective general surgery (GS) revealed that CRP was a more reliable parameter than white blood cell (WBC) counts [13][14][15]. It also reflects the degree of surgical stress or the current status of dogs with acute or chronic diseases [16][17][18][19].…”
Section: Introductionmentioning
confidence: 86%
“…Patellar luxation often requires surgery but does not cause severe trauma or inflammation by itself, as otherwise healthy dogs expecting surgery showed physiological CRP concentrations. Twenty-four hours after the surgery a 2–6-fold rise (median 92 μg/mL) was noted [ 86 ]. CRP may be a nonspecific biomarker for discospondylitis—but probably more sensitive than fever, leukocytosis, neutrophilia, and hyperglobulinemia.…”
Section: Orthopedic Diseasesmentioning
confidence: 99%
“…Thus, this particular assay was found to be sufficiently accurate and precise for clinical use. One study which served as a clinical validation of the Catalyst CRP assay found that it could reliably differentiate between the CRP concentrations of dogs that were pre‐ and postmedial patellar luxation surgery 33 …”
Section: Measurement Of Canine Crpmentioning
confidence: 99%